Effects of respiratory muscle training in soccer players: a systematic review with a meta-analysis - León-Morillas, F.; León-Garzón, M. C.; del Mar Martinez-Garcia, M.; Reina-Abellán, J.; Palop-Montoro, M. V.; de Oliveira-Sousa, S. L. (Sportverletzung Sportschaden, 2021)
Respiratory muscle training can improve strength and reduce respiratory muscle fatigue during high-intensity exercise. Little is known about the existing evidence in soccer players. A systematic review with a meta-analysis was performed to analyse the existing evidence on the effects of respiratory muscle training in soccer players. Two independent researchers reviewed 17 databases until July 2019. Inclusion criteria were controlled clinical trials (randomised or not), soccer players (professional or recreational), females and/or males, and respiratory muscle training compared with simulated or regular training groups. The methodological quality and quality of evidence were evaluated with the Cochrane Collaboration Tool and GRADE score, respectively. Statistical analysis was performed using the integral meta-analysis 3.3.070. Nine studies met the eligibility criteria. The meta-analysis was performed for eight variables related to respiratory muscle function, lung function and sports performance. Respiratory muscle training provided a significant improvement compared with simulated or regular training in maximal inspiratory buccal pressure (6 studies, SDM = 0.89; 95 % CI = 0.42, 1.35) and maximum consumption of oxygen (3 studies, SDM = 0.92; 95 % CI = 0.24; 1.61). No significant improvements were observed for other variables. The quality of the evidence was rated as low or very low.